Structural variations in (CuL)2Ln complexes of a series of lanthanide ions with a salen-type unsymmetrical Schiff base(H2L): Dy and Tb derivatives as potential single-molecule magnets. Issue 36 (30th August 2017) - Mahapatra, Prithwish; Ghosh, Soumavo; Koizumi, Naoki; Kanetomo, Takuya; Ishida, Takayuki; Drew, Michael G. B.; Ghosh, Ashutosh
Abstract : Five heterometallic Cu2 Ln complexes (Ln = Gd, Tb, Dy, Ho and Er) have been synthesized using asymmetric Schiff base ligand. Among these, Cu2 Tb and Cu2 Dy complexes show field induced SMM behaviour. Abstract : A new series of heterometallic trinuclear Cu2 Ln complexes [lanthanide ions Ln = Gd (1 ), Tb (2 ), Dy (3 ), Ho (4 ) and Er (5 )] has been synthesized using a Cu(ii )-metalloligand derived from a N2 O2 donor unsymmetrical Schiff base, H2 L (where H2 L = N -α-methylsalicylidene- N ′-salicylidene-1, 3-propanediamine), and structurally characterized. Among these complexes, [(CuL)2 Gd(NO3 )3 (CH3 CN)2 ] (1 ), [(CuL)2 Tb(NO3 )3 (CH3 CN)2 ] (2 ) and [(CuL)2 Dy(NO3 )3 (CH3 CN)2 ] (3 ) are isomorphic and isostructural. In these complexes two metalloligands coordinate to the central Ln(iii ) (Ln = Gd, Tb and Dy respectively) ion in a transoid fashion via μ2 -phenoxido oxygen atoms. The Ln(iii ) ions are deca-coordinated with a distorted tetradecahedron geometry. The two terminal Cu(ii ) ions of the complexes possess a hexa-coordinated distorted octahedral geometry. In contrast, in complexes [(CuL)2 Ho(NO3 )3 (CH3 CN)], (4 ) and [(CuL)2 Er(NO3 )3 (CH3 CN)]·0.5(CH3 CN) (5 ), the two metalloligands coordinated to the Ln(iii ) ions in a cisoid fashion. The Ho(iii ) ion in4 is nona-coordinated with a distorted tricapped trigonal prismatic geometry and the Er(iii ) ion in5 is octa-coordinated with a distorted square antiprismatic geometry. The two terminal Cu(ii ) ions in complexes4 and5 are penta-coordinated with a distorted square-pyramidal geometry. The dc magnetic susceptibilities and field dependent magnetization measurement of complex1 reveal the occurrence of ferromagnetic interactions between Cu(ii ) and Gd(iii ) ions as well as intermolecular antiferromagnetic interactions. Both complexes2 and3 show ferromagnetic interactions between Cu(ii ) and Ln(iii ) ions. The ac magnetic susceptibilities of all the complexes were also recorded and it was found that only complexes2 and3 exhibit slow relaxation of magnetization reorientation below 10 K at 2000 Oe applied dc field, this being characteristic of single molecule magnets.